A conserved sequence in the T-cell receptor beta-chain promoter region. - Anderson, S J (1988)
The antigen-specific receptors of T and B lymphocytes are distinct, though structurally related, molecules. During development, lymphoid cells assemble functional variable (V) region genes for each receptor chain from separate multimember gene families by somatic DNA rearrangements of individual germ-line segments. Transcription may play a role in regulating the tissue and stage specificity of these rearrangements by controlling the accessibility of germ-line loci to the recombinational machinery. Immunoglobulin V-region genes are transcribed from tissue-specific promoters that have been well characterized. We report here the characterization of 14 T-cell receptor beta-chain V-region gene promoters. Sequence analysis indicates that these promoters do not contain the conserved octamer that is located upstream of all immunoglobulin genes. However, a unique decanucleotide sequence, not present in immunoglobulin genes, is conserved in the promoter region of murine and human V beta genes. We identify this sequence as a potential regulatory element, based on its position, conservation, and sequence homology to sites known to bind transcription-activating factors. The possibility that the distinct structures of immunoglobulin and T-cell receptor gene promoters may contribute to the tissue-specific rearrangement and expression of receptor gene families is discussed.